Adaptability in Buffaloes during Spring and Summer Seasons in Eastern Plane Zone of Uttar Pradesh, India - Rai, Vikas; Choudhary, Pankaj K.; Kumar, Pramod; Maurya, Pankaj K.; Maurya, Satyendra K.; Kumar, Abhishek; Kumar, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Adaptability of buffaloes during spring and summer seasons in three districts of eastern plane zone of Uttar Pradesh was studied by different Heat tolerance indices like Ibrea heat tolerance coefficient (IHTC), Gaalaas heat tolerance test, Benezara coefficient of adaptability and Dairy search index. All parameters of heat tolerance indices were calculated by using different physiological parameters like rectal temperature, pulse rate and respiration rate. Temperature humidity index (THI) of all three districts was also calculated by using dry bulb temperature and humidity. There was a significant (p <0.01) difference in THI values in spring and summer seasons in all three districts. The IHTC values and Gaalaas values of buffaloes during spring season were nearer to 100 in comparison to summer season. Overall Means ± SEM of Benezara coefficient of adaptability and Dairy search index were more closure to 2 and 1, respectively, in spring season and summer season, and animals showed more adaptability in spring season in comparison to summer season.